Consumer Protection Analysis of the Use of Underhand PPJB in Pre Project Selling of Apartments - Dini Sasmitaningrum; Hanif Nur Widhiyanti; Erna Anggraini (State Islamic University of North Sumatra Indonesia, 2025)
This study examines the form of legal protection for apartment buyers through the pre-project selling (PPS) system that uses an underhand sale and purchase agreement (PPJB), a practice that is commonly carried out before the administrative and technical requirements as stipulated in the Apartment Law are fulfilled. The objectives of this study are to analyze the position and evidentiary strength of private PPJBs, the scope of developer liability in the event of default, and to assess whether the waarmerking mechanism is capable of providing adequate protection for consumers. Using a normative juridical research method through a legislative and analytical approach, this study assesses the gap between normative provisions and PPS practices in the field. The results of the study show that private PPJBs, although valid according to Article 1320 of the Civil Code, do not provide legal certainty because they are not verified by a notary and are often used before the fulfillment of permits and construction guarantees, thereby weakening the bargaining position of consumers in the event of project stalling or delays. This study concludes that the normative vacuum in Article 43 of the Apartment Law and the absence of sanctions against non-notarial PPJB create structural vulnerabilities, thus requiring regulatory strengthening, notarial PPJB obligations, and more effective preventive protection mechanisms.